2020
DOI: 10.21037/atm.2020.03.30
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of transcriptome data for identifying biomarkers and therapeutic targets in head and neck squamous cell carcinoma

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is one of the most common malignancy worldwide. Accumulating evidences have highlighted the importance of transcriptome data during HNSCC tumorigenesis. The aim of this study was to identify significant genes as effective biomarkers for HNSCC and constructed miRNA-mRNA regulatory network for a more comprehensive understanding of the underlying molecular mechanisms.Methods: A total of four independent microarrays conducted on HNSCC samples were downloade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…As a pathway to promote cell function, NF−kappa B signaling pathways activation may be related to the synthesis of viral proteins. In summary, the potential host-virus protein interactions may provide us with new ideas and strategies for drug screening and the development of drug-related research in SARS-CoV-2 [ 27 ]. At the same time, based on the PPI network diagram, we used the CytoHubba plug-in to select 12 central genes with high connectivity, all of which occupied the core nodes of the network, suggesting that these central genes might play a pivotal role in the process of infection in the novel coronavirus [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a pathway to promote cell function, NF−kappa B signaling pathways activation may be related to the synthesis of viral proteins. In summary, the potential host-virus protein interactions may provide us with new ideas and strategies for drug screening and the development of drug-related research in SARS-CoV-2 [ 27 ]. At the same time, based on the PPI network diagram, we used the CytoHubba plug-in to select 12 central genes with high connectivity, all of which occupied the core nodes of the network, suggesting that these central genes might play a pivotal role in the process of infection in the novel coronavirus [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The integration and analysis of differentially expressed genes (DEGs) and differentially expressed miRNAs (DEMs) based on microarray data are helpful to dig out diagnostic biomarkers and therapeutic targets. A study reported that a crucial miRNA-mRNA network involved neck squamous cell carcinoma to explore the underlying regulatory mechanisms [ 11 ]. Another study revealed that candidate miRNA-mRNA regulatory networks could be used to predict radioresistance in nasopharyngeal carcinoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al ( 31 ) used functional enrichment analysis to screen genes associated with improving invasive ductal carcinoma treatment and COL4A1 was found to be a key gene that influenced proliferation and invasion of the invasive ductal carcinoma cells. Other studies have shown that COL4A1 is upregulated in head and neck squamous cell carcinoma and may serve as a novel prognostic biomarker for the recurrence of OSCC ( 32 , 33 ), indicating that COL4A1 expression is associated with OSCC. In the present study, COL4A1 was highly expressed in several OSCC cell lines and COL4A expression was highest in SCC-4 cells, which may be associated with the high invasiveness, as well as migration, proliferation and differentiation, of SCC-4 ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 96%